Efectos del proceso inmediato sobre el derecho a probar del imputado en Iquitos año 2021 - Calderón Espinoza, Tania Violeta (2023)
The objective of this research work was to "Determine how the consequences of the immediate process in OAF cases affect the right to prove of the accused in the Collegiate Criminal Courts of the Superior Court of Justice of Loreto, year 2021." The methodology used was basic, descriptive, qualitative, legal - propositional. The population and sample were made up of Judges and Prosecutors and active Professionals, from the Judiciary and Public Ministry, included in the year 2021. Based on the results obtained, the hypothesis test was able to confirm that there is a significant incidence between the Immediate Process in the cases of OAF and the Right to prove of the accused in the JPC-CSJ, of Loreto, year 2021. In other words, the Immediate Process in OAF cases limits the right of defense of the accused, because in the practical scenario there are varied conditions, such as: the lack of foundation for the claim or the presentation of out-of-date evidence; Likewise, those interviewed consider that the principle of contradiction and equality of arms is violated if the accused is not given the opportunity to defend himself; and in the same way, they consider that the Principle of Contradiction and Equality of Arms is violated, by not leaving the option open for the accused to present his defense strategy. Therefore, it was concluded that, currently, malpractice is developing on the part of the operators, so that on repeated occasions the operators do not carry out the task of corroborating the data that demonstrates compliance with the payment. partial or total of the requested pension or if it was deducted from the payroll area of the company where you work.